2019
DOI: 10.1111/eea.12846
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomers of fuscumol acetate comprise the aggregation‐sex pheromone of the South American cerambycid beetle Psapharochrus maculatissimus, and likely pheromones of the cerambycids Eupromerella plaumanni and Hylettus seniculus

Abstract: There is increasing evidence that pheromone chemistry within the large coleopteran family Cerambycidae is often highly conserved, with numerous related species sharing the same pheromone components. As a result, traps containing these components can attract multiple cerambycid species simultaneously. In the present study, we exploited this concept in the identification of the male‐produced aggregation‐sex pheromone of the South American species Psapharochrus maculatissimus (Bates) (Coleoptera: Cerambycidae, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Semiochemicals (pher-ISSN On-Line: 1807-0205 ISSN Printed: 0031-1049 ISNI: 0000-0004-0384-1825 omone and plant volatiles) and UV light were used as attractants. Except for Psapharochrus maculatissimus (Bates, 1861) (i.e., Silva et al, 2019), it is noteworthy to point that cerambycid species reported here were caught at random by the treatment traps and at insufficient numbers for statistics (data not shown).…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Semiochemicals (pher-ISSN On-Line: 1807-0205 ISSN Printed: 0031-1049 ISNI: 0000-0004-0384-1825 omone and plant volatiles) and UV light were used as attractants. Except for Psapharochrus maculatissimus (Bates, 1861) (i.e., Silva et al, 2019), it is noteworthy to point that cerambycid species reported here were caught at random by the treatment traps and at insufficient numbers for statistics (data not shown).…”
Section: Methodsmentioning
confidence: 76%
“…In that occasion, conspecific adults of both sexes were caught with traps baited with general attractant pheromones for cerambycid beetles. Living adult beetles were used to obtain the attractant pheromone of the species and the results will be published elsewhere (i.e., Silva et al, 2019). Geographical distribution: This species was described from Jamaica.…”
Section: Remarksmentioning
confidence: 99%
“…Thus, it will likely be necessary to estimate which enantiomer of each compound is produced by each species through bioassays of the enantiomers, or possibly non-racemic mixtures of the two enantiomers of each component. Such tests may prove very revealing, given several recent examples demonstrating enantiomeric discrimination, and synergism between enantiomers, for several cerambycid species [14,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…For E. flexuosa and E. lenkoi, as soon as we found that the adults of both species were attracted by some treatment lures in the bioassays for E. assimilis (see Results), we deployed an extra set of four traps with the same attractants, to collect live adults of these species. We used cross-vane intercept panel traps (black corrugated plastic) hung from inverted L-shaped frames made from PVC pipe (for details see [14]). Rainwater was drained from the collection jars suspended below the traps by drilling 2-mm holes in the bottoms of the jars.…”
Section: Source Of Beetles For Collection Of Headspace Volatilesmentioning
confidence: 99%
See 1 more Smart Citation